A different shape grammar approach for automatic design generation - Santos, F. (2022)
This paper proposes a different approach for shape grammars where designs are exclusively generated through computations of symbols. This option has the advantage of supporting declarative knowledge and thus facilitates shape reasoning capabilities. Our approach also detached procedural knowledge from shape knowledge using procedural notions that capture sequences, alternatives and tests that should be applied during design process. This decision provides good modular specifications. Moreover, we follow a non-deterministic procedural perspective in the characterization of design processes. Its implementation supports exploratory automatic design generation. Differences between this approach and the conventional approach are discussed and a case study is explored.